Invertebrates and herptiles for livelihoods—ethnozoological use among different ethnic communities in Jammu and Kashmir (Indian Himalayas) - Hassan, Musheerul; Haq, Shiekh Marifatul; Amjad, Muhammad Shoaib; Ahmad, Riyaz; Bussmann, Rainer W.; Pérez de la Lastra, José Manuel (Frontiers in Pharmacology, 2023)
Background: Ethnic communities have relied on animals and their derived products for ages, and their use is often intricately related to many cultural features. In remote regions across the globe, indigenous peoples have been using invertebrates and herptiles for a variety of purposes (medicine, food, cultural, and spiritual importance), but scientific research on such use is scarce, particularly in the Western Himalayas. We collected use information on invertebrates and herpetofauna from Jammu and Kashmir-India across different native communities, i.e. Gujjar, Bakarwal, Dogra, Kashmiri and Pahari. Methodology: The data was gathered using semi-structured interviews followed by group discussions. The information gathered was analyzed using ordination techniques (Principal Component Analysis) and hierarchical cluster analysis. The venn diagram was used to investigate cross-cultural similarities and differences between ethnic groups. Results: We documented 30 species belonging to 5 classes and 20 families used for medicinal, magical-religious, food, costume, religious, omen, poultry, and agricultural purposes. The use of fauna resources varied across ethnic groups. The cross-cultural examination revealed that traditional knowledge was more prevalent among Kashmiri and Pahari ethnic groups. The maximum numbers of species (27%) were uniquely used by Kashmiri, followed by Pahari (17%), and least by Dogra (3%).The ethnozoological use of all documented species is unprecedented. In addition to ethnozoological usage, various documented species (Apis cerana, Apis mellifera, Hirudinaria granulosa, and Bombyx mori) were also important for the local population's livelihoods. Conclusion: Our findings are pioneering and can be considered the baseline for further understanding of invertebrates and herptiles in the selected region, which can then be used for community development.